2007
DOI: 10.1097/cji.0b013e318046f396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Serum and Serum-free Media for Generation of Clinical Grade DCs

Abstract: Dendritic cells (DCs) are the most potent antigen presenting cells and are therefore widely used in cancer immunotherapy. An optimal method for the generation of DCs for clinical use remains to be established. The aim of the study was to find a serum-free media (SFM) able to generate reproducible and functional cultures of DCs for clinical studies. We characterized immature and mature DCs cultured in SFM, CellGro DC and X-VIVO15, and serum media (SM), RPMI 1640+5% human serum or autologous serum. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
(69 reference statements)
4
23
0
1
Order By: Relevance
“…As expected, an increased dextran uptake by iDCs (day 6 culture) was observed compared with the day 8 mDCs; however, the increase was not statistically significant. Various studies have indicated that the uptake of dextran may be a measure of immune response (23)(24)(25). The present results also support earlier studies that suggest that increased antigen uptake is associated with IL-12 and IFN-Ī³ secretion, and CTL response (17,26,27).…”
Section: Discussionsupporting
confidence: 90%
“…As expected, an increased dextran uptake by iDCs (day 6 culture) was observed compared with the day 8 mDCs; however, the increase was not statistically significant. Various studies have indicated that the uptake of dextran may be a measure of immune response (23)(24)(25). The present results also support earlier studies that suggest that increased antigen uptake is associated with IL-12 and IFN-Ī³ secretion, and CTL response (17,26,27).…”
Section: Discussionsupporting
confidence: 90%
“…These clinical-grade tolDCs are comparable to our previously characterised research-grade tolDCs24 25 in terms of cell surface phenotype, cytokine production and in vitro T cell modulatory function. CellGroDC was deemed the medium of choice23 and is currently used in DC vaccine development for cancer 38ā€“40. MPLA, a low-toxicity alternative to LPS, is currently being tested in vaccine development 41.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with tolDCs therefore has great potential for the treatment of autoimmunity in humans, and the current challenge is to develop tolDCs for clinical application. Others have addressed the development of clinical-grade DCs for cancer immunotherapy 21ā€“23. However, criteria for the development of safe tolDCs for the treatment of autoimmune disease remain to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent avenues that are being pursued is the use of DCs. Cell therapy remains extremely complex and the quality of cells produce strictly depends on methods and materials adopted 52.…”
Section: Novel Strategiesmentioning
confidence: 99%